MEKANISME PEMBUKAAN DAN PENUTUPAN REKENING TABUNGAN PADA ANAK USIA DINI DI BANK SYARIAH(Studi pada PT Bank Muamalat Kabupaten Bone) - masyhuri, masyhuri; Putri, Juliandari (Islamic Banking and Finance, 2022)
A bank is a financial institution whose main business is to raise funds, distribute funds, and provide services in payment traffic and money circulation. Islamic banking as an institution that collects and distributes funds has various types of businesses that offer various conveniences for the public to meet the needs of business capital, consumptive needs, future savings, and just meet entertainment needs. Mechanism is a process of carrying out an activity carried out by a person or several people using orders and rules as well as the flow of communication and division of tasks in accordance with professionalism. This study aims to find out how the mechanism for opening and closing savings accounts in early childhood in Islamic banks, and to find out how savings law in early childhood is in an Islamic economic perspective. Based on the purpose of the study, this research is a type of qualitative research using a grounded theory approach. This technique is used to describe the data that researchers collect, both data from interviews, observations and documentation during research at "PT. Bank Muamalat Bone Regency". The results of this study show that the mechanism for opening and closing accounts in early childhood savings is on the condition that the identity of the child who wants to open a savings account must already have a birth certificate and have been recorded in the family card, and the contract system used in this savings is to use a wadiah contract in the form of a entrustment